Compreensão e produção oral de interrogativas-Q em crianças portuguesas surdas com implante coclear - Moita, Mara; Lobo, Maria (Revista da Associação Portuguesa de Linguística, 2018)
The present study investigates the comprehension and production of Portuguese wh-questions by hearing impaired children with cochlear implants. We investigate whether the asymmetries found in typically developing children are also present in our target group or whether the difficulties are more widespread. In particular, we investigate whether there are asymmetries between subject and (DP/PP) object wh-questions produced by these children, and whether wh-questions with a lexical restriction are more difficult than bare wh-questions. We also consider the importance of extra-linguistic variables, such as age of implantation, hearing age, early attendance of speech and language therapy sessions, and exposure to sign language.